2022
DOI: 10.1021/acsami.1c19617
|View full text |Cite
|
Sign up to set email alerts
|

Ginger and Garlic Extracts Enhance Osteogenesis in 3D Printed Calcium Phosphate Bone Scaffolds with Bimodal Pore Distribution

Abstract: Natural medicines have long been used to treat physiological ailments where both ginger (gingerol) and garlic (allicin) are key players in immune system promotion, reduction in blood pressure, and lowering inflammation response. With their efficacy in bone healing, these compounds have great value as medicinal additives in bone scaffolds for localized treatment to support tissue formation, along with providing their natural therapeutic benefits. Utilization of 3D-printed (3DP) bone tissue engineering scaffolds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 48 publications
3
25
0
Order By: Relevance
“…TRAP enzyme is secreted by the osteoclast cells during bone resorption, and it is a marker to quantify osteoclastic activity. 70 Our results show a significant decrease in TRAP expression in presence of Mg 2+ and curcumin. This behavior is possible because of two reasons (a) there are fewer viable cells on the treatment samples (b) the cells are not attached well to the scaffold surface, and they are unable to resorb the TCP, followed by releasing TRAP.…”
Section: Multifunctional Scaffold Design Strategies By 3d Printingsupporting
confidence: 49%
See 1 more Smart Citation
“…TRAP enzyme is secreted by the osteoclast cells during bone resorption, and it is a marker to quantify osteoclastic activity. 70 Our results show a significant decrease in TRAP expression in presence of Mg 2+ and curcumin. This behavior is possible because of two reasons (a) there are fewer viable cells on the treatment samples (b) the cells are not attached well to the scaffold surface, and they are unable to resorb the TCP, followed by releasing TRAP.…”
Section: Multifunctional Scaffold Design Strategies By 3d Printingsupporting
confidence: 49%
“…The growth of new blood vessels results in nutrient supply to the newly grown bone segment. 70 Our quantification results (Fig. 8) reveal that the presence of MgO helps to significantly enhance blood vessel formation as compared to the control.…”
Section: Multifunctional Scaffold Design Strategies By 3d Printingmentioning
confidence: 73%
“…However, MG-63 cells are osteoblasts derived from osteosarcoma, a malignant bone tumors, thus are not fully representative of physiological osteoblasts (122). Increased cells proliferation by Allium genus was also shown by ginger and garlic extracts released by 3D-printed calcium phosphate scaffolds on human fetal osteoblast cells (82); increased osteogenesis by Allium fistulosum was also shown in the mouse C57BL/6 osteoblastic calvaria cell line (MC3T3-E1) (80). Up to date no studies on primary cultures of human MSCs have been performed with extracts derived from Alliaceae or Brassicaceae.…”
Section: Edible Plantsmentioning
confidence: 99%
“…Using human THP1 monocytes, Bose et al. showed that ginger and garlic extracts reduce the frequency and the size of resorption pits carved by osteoclasts ( 82 ); inhibition of osteoclast number was found also by onion and commercial onion extracts in rat and rabbit osteoclasts ( 81 ). Notably, Wetli et al.…”
Section: Effect Of Oscs On Bone Tissue: Preclinical Evidencementioning
confidence: 99%
See 1 more Smart Citation